ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH (SAK EMKM) DAN ASAS KEBERLANJUTAN USAHA PADA USAHA MIKRO, KECIL, DAN MENENGAH - yuliana - tambariki (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Micro, Small and Medium Enterprises (MSMEs) have minimal understanding of financial recording and reporting in accordance with currently applicable standards, so the aim of research in this thesis is to find out how MSMEs understand the importance of preparing financial reports in accordance with the Financial Accounting Standards for Micro, Small Entities. , and Medium (SAK EMKM), readiness of MSMEs to implement SAK EMKM in their financial reports, implement financial report recording according to the accrual basis concept, apply the business entity concept, and have adequate resources. This research uses a qualitative approach with a case study research method and is descriptive in nature. This research aims to determine the extent of implementing and analyzing the implementation of Financial Accounting Standards for Micro, Small and Medium Entities (Sak Emkm), analyzing aspects of Going Concern or the sustainability of Micro, Small and Medium Enterprises (Sak Emkm) in Micro, Small and Medium Enterprises. And Medium implemented by 8 MSMEs in Paal 4 sub-district can have sustainable business value that can survive. The results of research on financial reports prepared by MSMEs with financial reports based on SAK EMKM regarding the presentation of financial reports show that there are still accounts that are not appropriate because the presentation of account names and measurements are not in accordance with the applicable SAK EMKM. This error occurs because MSMEs do not update their knowledge about developments in current financial accounting standards, this is due to inadequate human resources. This is supported by evidence that the results of the comparison table show that there are still MSMEs that do not prepare complete financial reports in accordance with SAK EMKM.